Analysis of the Influence of Brand Communication, Brand Image and Brand Personality on Brand Trust in The Body Shop Products - Dhikriyah, Laeli; Sukresna, I Made (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the effect of brand communication variables, brand image, brand trust on the brand trust of The Body Shop products. This research is a quantitative research The data sources used in this research are primary data and secondary data. The sampling applied in this study uses a method called the Non Probability Sampling technique. This research make use of Structural Equation Modeling (SEM) as a statistical instrument in an effort to test various hypotheses that have been determinedwith the help of AMOS software. The results showed thatBrand communication has a positive effect on brand image, brand image has a positive effect on brand personality, meaning that the better the brand image of a product will affect the brand personality. The results also show that Brand communication has a positive effect on brand trust, meaning that brand communication has no influence on brand trust and brand image has a positive effect on brand trust and that the better the brand image created by a product will increase trust in consumers and brand personality has a positive effect on brand trust. . Keywords : Brand Communication; Brand Image; Brand Trust